Dampak Perencanaan Pajak, Beban Pajak Tangguhan, dan Ukuran Perusahaan Terhadap Manajemen Laba - Purba, Lidia Margaretta; Nuryati, Tutty; Yulaeli, Tri; Nurbaiti, Beti; Ningrum, Endah Prawesti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Many investors invest in a company with the aim of obtaining financial benefits in the future. To evaluate the company's performance, investors can refer to the information presented in the financial statements. One of the main indicators used in financial statements to assess the company's performance is profit. Therefore, profit is often the object of manipulation by management, either to increase or decrease its value, through the presentation of inappropriate data in the financial statements. This practice is known as earnings management. This study reviews the effect of tax planning, deferred tax burden and company size on earnings management. The purpose of writing this article is to develop a hypothesis about the influence between variables for use in further research. The results of the research based on literature reviews in several previous research journals prove that: Tax planning has an effect on earnings management, Deferred tax burden has an effect on earnings management, and Company size has an effect on earnings management.